TEACHING PRACTICE OF DAOQING SHADOW PLAY IN HUAN COUNTY, CHINA - SOME REFLECTIONS ON NOTATION - Qiang Zhanquan; Raja Iskandar Raja Halid (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Daoqing shadow play in Huan County, as an important part of Chinese shadow play, has been attached importance by the local government and schools. At present, Longdong University has built a relatively complete shadow play curriculum system, which makes it a model for the inheritance of shadow play in colleges and universities. In the teaching practice of shadow play and a large number of literature reviews, researchers found that the music score of shadow play is a few fragments, which only records the singing part of the monophonic music, and there is no total score that can fully present the whole picture of shadow play music. Based on the theory of C. Seeger descriptive notation, this paper explains the characteristics of shadow play music in rhythm, beat, time and intonation by recording and analyzing it. In the background of local culture of Huan County, the author thinks about the rhythm, rhythm, sentence reading and dialect tuning, and expounds the methods and key points of recording the music score of Huan County Daoqing shadow play.